Risk factors identified in users subject to cardiac catheterization (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.12522The objective was to identify risk factors for cardiovascular disease present in patients undergoing cardiac catheterization. Documentary study, a retrospective, quantitative nature. Developed in the hemodynamic of a public hospital in Fortaleza, Ceará State, Brazil. We analyzed the records of 1269 patients undergoing cardiac catheterization. The data was collected by a program called teleficha existing in that hospital. Data were organized in tables and graphs. The study was approved by the Ethics Committee. The results were: 819 (65%) patients were male and the average age was 62 years old. It was identified as risk factors: hypertension (73%), dyslipidemia (44%), smoking (37%), heredity (25%) and diabetes mellitus (16%). It was concluded that existed a high prevalence of risk factors for cardiovascular disease in the population studied, showing the need for health education programs, aimed to clarify and control the risk factors of cardiovascular diseases.